2019
DOI: 10.2134/age2018.10.0052
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate‐Resistant Soybean Response to Micro‐Rates of Three Dicamba‐Based Herbicides

Abstract: Core Ideas The impact of simulated dicamba drift on growth and yield of glyphosate‐resistant soybean was similar among dicamba formulations. The impact of dicamba drift on soybean could be influenced by moisture condition of the environmental field. Late vegetative or early flowering stage of soybean was the most sensitive growth stage to dicamba drift. New dicamba‐based herbicides such as Engenia (N,N‐bis‐(3‐aminopropyl) methylamine salt) and XtendiMax (diglycolamine salt) with VaporGrip technology were dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 22 publications
8
44
1
Order By: Relevance
“…Dimethylamine (DMA) salts are known to be the most volatile, while diglycolamine (DGA) salts are less volatile [4]. The newest additions to the benzoic acid family consist of a DGA salt of dicamba with the trade name XtendiMax ® (Bayer CropScience LP, 800 Lindbergh Blvd., Saint Louis, MO, USA) and an (N,N-bis-(3-aminopropyl) methylamine salt) (BAPMA) salt of dicamba with the trade name Engenia ® (BASF Corporation, 26 Davis Drive, Research Triangle Park, NC, USA) [5]. While DGA and BAPMA salts are less volatile than their DMA predecessor, they can still volatilize [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethylamine (DMA) salts are known to be the most volatile, while diglycolamine (DGA) salts are less volatile [4]. The newest additions to the benzoic acid family consist of a DGA salt of dicamba with the trade name XtendiMax ® (Bayer CropScience LP, 800 Lindbergh Blvd., Saint Louis, MO, USA) and an (N,N-bis-(3-aminopropyl) methylamine salt) (BAPMA) salt of dicamba with the trade name Engenia ® (BASF Corporation, 26 Davis Drive, Research Triangle Park, NC, USA) [5]. While DGA and BAPMA salts are less volatile than their DMA predecessor, they can still volatilize [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various formulations of dicamba have been approved for use in DR soybean cultivars [5]. Applications of dicamba made in proximity to peanut can cause injury and reduce yield [5,30,31]. Therefore, a field study was conducted in 2017 and 2018 to evaluate peanut response to low rates of dicamba at three reproductive growth stages.…”
Section: Introductionmentioning
confidence: 99%
“…Osipitan et al. (2019) showed that three dicamba‐containing formulations (BAPMA, DGA, and DGAvg) equally reduced the yield of non‐DT soybean (cv. Pioneer P24T19R).…”
Section: Resultsmentioning
confidence: 99%
“…The extent and severity of a drift event is a result of complex factors including spray application parameters, environmental conditions, herbicide formulation and rate, crop growth stage, and crop sensitivity (Heidary, Douglaz, Sinfort, & Vallet, 2014; Lofstrom et al., 2013). Numerous research studies investigated how soybean symptomology and yield reduction are correlated to crop growth stage during drift exposure events (Auch & Arnold, 1978; Griffin, Bauerle, Stephenson, Miller, & Boudreaux, 2013; Kelly et al., 2005; Osipitan, Scott, & Knezevic, 2019; Solomon & Bradley, 2014; Thompson & Egli, 1973; Wax et al., 1969). However, few of these studies have provided results pertaining to the differences in herbicide sensitivity across cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is potential for off-target movement that may result in damage to other adjacent, sensitive broadleaf plants. Although injury from low rates or simulated drift rates of several herbicides has been reported in many crops, dicamba and 2,4-D drift are of particular concern due to great potential of crop injury [49][50][51][52]. Plant response to these PGR herbicides is easily recognized as leaf cupping and crinkling and/or epinasty, and very low rates of herbicide may cause injury in susceptible plants [53].…”
Section: New Herbicide Trait Technologies and Developing Environmentamentioning
confidence: 99%